Behavioral Models on the Playersâ€™ Activities during the Tennis Matches - Prodan, Rodica; Grosu, Emilia Florina (Arena-Journal of Physical Activities, 2017)
The individual sport gamesâ€”given their characteristicsâ€”impose constraints on behavior, constraints in relation to which some actions tend to produce good and other actions harm or at least lesser amounts of good. Therefore, in the last decades there was a lot of discussion whether certain behavior should be considered Fair Play. The dominant paradigm on ethical behavior presented in 1986 by J. Rest (Rest, 1986), despite its age, it is still the leading model for studying ethical behavior (Craft, 2013). This study is aimed to answer two questions: How can we act ethically in sport? And why would we want to be ethical competitors in the first place? The starting point of the study is the conceptualization of the term Fair Play as either â€œrespect for the rulesâ€ or â€œrespect for the spirit of the gameâ€, as well as by other determinants. The author analyzes the act of thinking, followed by a parallel between the tennis games and the stories found in the literature. Next is brought into the discussion the importance of challenges or tests as a result of impediments (hurdles) and objectives (goals). It is emphasized the position of the play- ers as testing collaborators, not necessarily contesting opponents. Instead of competitiveness (a commitment to try to surpass) and sportsmanship (a com- mitment to civility, fairness, if not generosity), two other virtues come to mind under the umbrella of testing obligations. One is determination; the second is impartiality or justice. The conclusion is that it canâ€™t be known if the chaotic-constrained patterns of evolution will continue to produce people who are meaning-seeking, story- telling human-beings, or who will see only the constraints that were visible to human intelligence around the year 2000 AD, or who will think that the connections between themselves and game playing are particularly gratifying ones.